PENGARUH GROSS DOMESTIC PRODUCT, INFLASI, SUKU BUNGA, MONEY SUPPLY, CURRENT ACCOUNT DAN CAPITAL ACCOUNT TERHADAP NILAI KURS RUPIAH INDONESIA – DOLLAR AMERIKA - Yunika Murdayanti (Jurnal Ilmiah Econosains, 2012)
Abstract Since free-floating exchange rate system has been applied in Indonesia on August 1998, the accumulation of depreciation of rupiah against the US dollar has been about 48,7% until December 2001. This condition brings many argumentations about the reasons behind the exchange rate instability faced by Indonesia among many experts whether it is caused by economic factors or by non-economic factors. By recognizing the causes, it will be easier for the experts and government of Indonesia to formulate the solution. This research is intended to analyze the influence of economic variables, i.e. Gross Domestic Product, money supply, interest rate, inflation rate, Current Account & Capital Account in both Indonesia and The United State of America, as well as the position of the balance of international payment of Indonesia to the exchange rate movement in order to give contributions to solve the problem. Based on the result money supply becomes the only variable which has a multicollinearity and excluded from the regression linear. Also only current account is not significant influence on the exchange rate movement, instead of the other variables. Coefficient of determination of the research model is 84.4 %, means that other factors, not accommodated in this research, give 15.6 % influence to the exchange rate movement. These other factors can be catagorized as other economic factors or non-economic factors. Keywords: exchange rate, Gross Domestic Product, money supply, interest rate, inflation rate, Current Account, Capital Account